2021
DOI: 10.1080/14728222.2021.1869213
|View full text |Cite
|
Sign up to set email alerts
|

The potential for immune checkpoint modulators in cerebrovascular injury and inflammation

Abstract: Introduction: Neuroinflammation has been linked to poor neurologic and functional outcomes in many cerebrovascular disorders. Immune checkpoints are upregulated in the setting of traumatic brain injury, intracerebral hemorrhage, ischemic stroke, central nervous systems vasculitis, and post-hemorrhagic vasospasm, and are potential mediators of pathologic inflammation. Burgeoning evidence suggests that immune checkpoint modulation is a promising treatment strategy to decrease immune cell recruitment, cytokine se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 164 publications
(122 reference statements)
0
15
0
Order By: Relevance
“…Recently, the inflammatory immune response has been shown to participate in all stages of the pathological progression of IS, including the production of inflammatory mediators and the chemotaxis of immune cells ( 5 ). After IS, an insufficient blood supply deprives brain cells of glucose and oxygen and disrupts the homeostasis of cells, thereby triggering pathophysiological processes, including excitotoxicity, oxidative stress, inflammation, apoptosis and cell death ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the inflammatory immune response has been shown to participate in all stages of the pathological progression of IS, including the production of inflammatory mediators and the chemotaxis of immune cells ( 5 ). After IS, an insufficient blood supply deprives brain cells of glucose and oxygen and disrupts the homeostasis of cells, thereby triggering pathophysiological processes, including excitotoxicity, oxidative stress, inflammation, apoptosis and cell death ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Data from a variety of studies demonstrate that post-injury inflammation (such as that seen following ischaemia and/or trauma) is associated with high levels of activated T cells and high levels of immune-checkpoint expression 186 . However, functional studies differ regarding whether PD-1–PD-L1 inhibition or gene knockout is either protective 187 or detrimental in this setting 188 .…”
Section: Effects On Other Immune Processesmentioning
confidence: 99%
“…67 Additionally, recent work has suggested the possibility of using immune checkpoint blockades as a potential drug target for limiting neuroinflammation following TBI or other neurological insults. 68 However, attempts to treat neurotrauma with anti-inflammatory agents have generally yielded poor results. 69 For example, the 6-month outcome results from the Corticosteroid Randomization After Significant Head Injury (CRASH) Trial showed that patients who were treated with corticosteroids after TBI had a higher risk of death or severe disability than patients who were treated with placebo.…”
Section: Is There An Adaptive Role Of Postinjury Immune Suppression?mentioning
confidence: 99%